2022
DOI: 10.1155/2022/9148257
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Ketoglutarate Alleviates Neuronal Apoptosis Induced by Central Insulin Resistance through Inhibiting S6K1 Phosphorylation after Subarachnoid Hemorrhage

Abstract: Neuronal apoptosis after subarachnoid hemorrhage (SAH) is believed to play an important role in early brain injury after SAH. The energy metabolism of neuron is closely related to its survival. The transient hyperglycemia caused by insulin resistance (IR) after SAH seriously affects the prognosis of patients. However, the specific mechanisms of IR after SAH are still not clear. Studies have shown that α-KG takes part in the regulation of IR and cell apoptosis. In this study, we aim to investigate whether α-KG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The interaction of IR and oxidative stress may contribute to influence AIS development. Finally, previous studies have shown that IR could inhibit glucose translocator 4 membrane translocation, leading to neuronal apoptosis due to insufficient glucose uptake 21 …”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The interaction of IR and oxidative stress may contribute to influence AIS development. Finally, previous studies have shown that IR could inhibit glucose translocator 4 membrane translocation, leading to neuronal apoptosis due to insufficient glucose uptake 21 …”
Section: Discussionmentioning
confidence: 92%
“…Finally, previous studies have shown that IR could inhibit glucose translocator 4 membrane translocation, leading to neuronal apoptosis due to insufficient glucose uptake. 21 In a survey of the general population based on the Northeast China Rural Cardiovascular Health Study and the National Stroke Screening and Intervention Program in Liaoning, Du et al 11 found a linear association between TyG-BMI levels and ischemic stroke risk. As the level of TyG-BMI increased, the risk of ischemic stroke significantly increased (P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our team found that IR inhibits GLUT4 membrane translocation, leading to the apoptosis of neurons due to insufficient glucose uptake. Inhibiting neuronal IR attenuates neuronal apoptosis ( 100 ). All of this suggests that IR could cause neuronal death.…”
Section: How Ir Affects the Progression Of Ischemic Strokementioning
confidence: 99%
“…This conflicting outcome indicates that statins for insulin resistance still require additional experimental confirmation. Apart from this, several medicines (e.g., α-ketoglutarate, astaxanthin) can reduce IR and increase neuronal survival by decreasing aberrant serine phosphorylation of IRS1 directly via inhibiting mTOR/S6K1 ( 100 , 128 ). In summary, there is substantial evidence that insulin sensitizers can boost brain insulin sensitivity, successfully treat ischemic stroke, and improve neurological function.…”
Section: How To Treat Ir In Ischemic Stroke Patientsmentioning
confidence: 99%
“…Neuronal death is considered a major cause of EBI ( Macdonald and Schweizer, 2017 ). Hence, a reduction in the number of neuronal deaths could improve nerve dysfunction and eventually improve the prognosis of patients ( Dong et al, 2016 ; Ding et al, 2022 ). Thus, further study on the mechanism of EBI and neuronal death is vitally important.…”
Section: Introductionmentioning
confidence: 99%